Noordbrabants Historisch Jaarboek 39 handelingen van het XIXde Colloquium 'De Brabantse Stad' : Brussel, 15 en 16 oktober 2021 : stad en territorium : de perceptie en representatie van stad en vorstendom in Brabant - Bijsterveld, Arnoud-Jan; Broers, Erik-Jan; Caspers, Charles; Daemen, Florian; De ruysscher, Dave; Douma, Klaasje; van Kooten, Rogier; Leenders, Karel; Toorians, Lauran; Vermeer, Mark (Noordbrabants Historisch Jaarboek, 2022)
This colloquium focuses on urban and princely space in the Duchy of Brabant in the late Middle Ages and early modern period. The focus is on how territorial developments were perceived in different social milieus. After all, urban elites, the monarch and his entourage had different - but sometimes similar - opinions about what Brabant actually was and used various media to communicate their ideas about it. Administrative, narrative and cartographic sources, architecture, literature and art bear witness to this. The Belgian-Dutch "Stichting Colloquium De Brabantse Stad" organizes an international meeting every three years at which various aspects of the history of the cities and of urban life in the old Duchy of Brabant are examined. The colloquium is organized alternately in the provinces of Antwerp, Flemish Brabant, Walloon Brabant, North Brabant and in the Brussels Capital Region. The XIXth colloquium, taking place in Brussels at the Université Saint-Louis, is being organized in cooperation with the NWO research project Imagining a territory.